sms gatway Sistem Informasi Pencari Kerja Dengan Penerapan SMS Gateway Pada Universitas Sjakhyakirti - Paisal Paisal (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2021)
Sjakhyakirti University is a business entity engaged in education in the Palembang region. Sjakhyakirti University always strives to provide good service for its students, both services in administration, learning process, and work distribution, because Sjakhyakirti University is a university that has a vision and mission to develop the nation's children. In order to make it easier for alumni to receive information about job vacancies, it is necessary to create a system that can provide information for alumni that can be received via SMS. SMS Gateway can send messages to hundreds of alumni numbers that have been stored in the database automatically and quickly without having to type messages and numbers on cell phones from alumni of Sjakhyakirti University. So the author will raise this thesis research with the title "Development of Job Seekers Information Systems With the Implementation of Sms Gateway at Sjakhyakirti University